2014
DOI: 10.1016/j.amjcard.2013.09.039
|View full text |Cite
|
Sign up to set email alerts
|

Relation of Thoracic Aortic Distensibility to Left Ventricular Area (from the Multi-Ethnic Study of Atherosclerosis [MESA])

Abstract: Decreased arterial compliance is an early manifestation of adverse structural and functional changes within the vessel wall. Its correlation with left ventricular (LV) area on computed tomography (CT), a marker of LV remodeling, has not been well demonstrated. We tested the hypothesis that decreasing aortic compliance and increasing arterial stiffness is independently associated with increased LV area. The study population consisted of 3,540 (61±10 years, 46% men) from the MESA study who underwent aortic diste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…The compliance of the two gel tubes was very close to the typical vascular compliances (namely, distensibility in some literature) of aortic and main pulmonary arteries in health and hypertension patients. 5,29 To our knowledge, it is the first time that hydrogels were fabricated into tubes with mimicked stiffness as native vessels.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The compliance of the two gel tubes was very close to the typical vascular compliances (namely, distensibility in some literature) of aortic and main pulmonary arteries in health and hypertension patients. 5,29 To our knowledge, it is the first time that hydrogels were fabricated into tubes with mimicked stiffness as native vessels.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Blood vessels show unique mechanical properties at a high elasticity , and strength, as they need to go through considerable deformations and stress fluctuations as part of the functions . An alteration of mechanical properties, especially increase of the stiffness, has long been known to relate with adverse cardiovascular outcomes such as hypertension and atherosclerosis . Mediators of these processes are usually uncoupled with other factors (e.g., hemorheological and chemical signals) in vivo, so that in vitro vascular models are needed to mimic and study the local vascular microenvironments.…”
Section: Introductionmentioning
confidence: 99%
“…Decreased arterial compliance, estimated by aortic distensibility measured by magnetic resonance imaging in the MESA study has also been shown, even after adjustment for risk factors, CAC, and C-reactive protein to be associated with increased left ventricular area (each standard deviation decrease in aortic distensibility associated with an 18 cm 2 increase in left ventricular area) [83]. Moreover, reduced aortic distensibility was shown in another report from the MESA study to be associated with increased odds of retinal arteriolar narrowing (odds ratio 1.7) even after adjustment for risk and inflammatory factors and other measures of subclinical disease [84].…”
Section: The Aortamentioning
confidence: 99%
“…Elevated measures of arterial stiffness (central and peripheral) have been shown to negatively impact LV systolic and diastolic function, impair coronary blood flow, and have been identified as a risk factor for cardiovascular disease and mortality [1][2][3][4][5][6][7][8][9]. One possible mechanism for these findings is that increased arterial stiffness can create additional LV work while simultaneously making coronary perfusion less efficient.…”
Section: Introductionmentioning
confidence: 99%